A Study to Evaluate Prognostic Factors and Define a Critical Volume for Early Surgery in Patients with Bifrontal Brain Contusions - Manoranjitha Kumari M; T.P. Jeyaselva Senthilkumar; Yamunadevi Ravi (Indian Journal of Neurosurgery)
Aim The aim of this study was to evaluate various prognostic factors and their impact on the outcome of patients with bifrontal brain contusions and to define the critical volume of bifrontal brain contusions and to advice early surgery